2019
DOI: 10.3390/md17120650
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Interactions of Sulfur-Containing Histidine Compounds with Human Gamma-Glutamyl Transpeptidase

Abstract: Gamma-glutamyl transpeptidase (GGT) is a cell surface enzyme involved in glutathione metabolism and maintenance of redox homeostasis. High expression of GGT on tumor cells is associated with an increase of cell proliferation and resistance against chemotherapy. GGT inhibitors that have been evaluated in clinical trials are too toxic for human use. We have previously identified ovothiols, 5(Nπ)-methyl-thiohistidines of marine origin, as non-competitive-like inhibitors of GGT that are more potent than the known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…The present work might provide the basis for a possible eco-sustainable production of ovothiols by diatoms, to be used as “biofactories” for biotechnological purposes through the light modulation of their growth, metabolism and physiology [ 3 , 7 , 19 , 61 , 62 , 63 ]. Indeed, despite the increasing interest in the pharmaceutical potential of this class of molecules endowed with antiproliferative, anti-inflammatory and antifibrotic properties [ 30 , 31 , 32 , 33 , 34 , 35 ], studies regarding their bioactivities are still limited by the small amounts of ovothiol available for applied research. Currently, they can be extracted by sea urchin eggs, thus obtaining 2.5 mg of pure ovothiol A from 10 g of wet material [ 25 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work might provide the basis for a possible eco-sustainable production of ovothiols by diatoms, to be used as “biofactories” for biotechnological purposes through the light modulation of their growth, metabolism and physiology [ 3 , 7 , 19 , 61 , 62 , 63 ]. Indeed, despite the increasing interest in the pharmaceutical potential of this class of molecules endowed with antiproliferative, anti-inflammatory and antifibrotic properties [ 30 , 31 , 32 , 33 , 34 , 35 ], studies regarding their bioactivities are still limited by the small amounts of ovothiol available for applied research. Currently, they can be extracted by sea urchin eggs, thus obtaining 2.5 mg of pure ovothiol A from 10 g of wet material [ 25 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ovothiols have been receiving great interest for their biological activities in in vitro and in vivo human model systems. Indeed, they exhibited pleiotropic beneficial properties, revealing antifibrotic activities in a murine model of liver fibrosis [30,31], antiproliferative action in human cancer cell lines [32][33][34] and anti-inflammatory effects in endothelial cells derived from women affected by gestational diabetes [35]. Ovothiols are synthesized in vivo by two key enzymes, the sulfoxide synthase OvoA and the β-lyase OvoB [36,37], in three different forms, A, B and C, differing in the methylation state of the α-amino group.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is required to identify the precise role of serum GGT and explore the utility of its kinetics as a prognostic biomarker in patients with GU cancer. Furthermore, less toxic uncompetitive inhibitors of GGT, such as OU749 and ovothiols, have the potential to become therapeutic agents for targeted therapy in patients with tumors with GGT-overexpression [ 67 , 68 , 69 , 70 ]. Future prospective clinical trials of GGT blockade therapies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Ovothiols, which are histidine-derived thiols isolated from sea urchin eggs, are known to protect the eggs from high oxidative stress at fertilization and may induce autophagy-dependent cell death in human hepatic cancer cells with high GGT expression while leaving normal cells unaffected [ 68 ]. Current studies have revealed that the uncompetitive GGT-inhibitory properties of ovothiols produced by marine invertebrates provide great promise for improving molecular-targeted therapy for GGT-positive malignancies, including GU cancer [ 69 , 70 ]. Clinical trials and optimization of these less toxic GGT inhibitors are warranted for the development of novel treatments.…”
Section: Potential Clinical Application Of Ggt Inhibitorsmentioning
confidence: 99%
“…Indeed, the development of new beneficial products, overcoming the side effects of common medicines, has attracted great interest in the pharmaceutical and nutraceutical sectors [ 158 ] for the development of new natural products from poorly exploited sources. A good deal of attention has been given the use of sulfur-containing compounds as alternative biomolecules in support of traditional medicine in common human disorders [ 159 , 160 , 161 , 162 , 163 , 164 ]. At the same time, moderate and controlled physical activity has always been seen as a support for the prevention of degenerative, cardiovascular and muscular diseases; as well as to prevent premature aging [ 57 ].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%